2009
DOI: 10.1007/s00296-009-0851-5
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of smoking in fibromyalgia patients and its association with symptoms

Abstract: The objective of the study was to determine the frequency of smoking in fibromyalgia (FM) and rheumatoid arthritis (RA) patients and investigate its association with the symptoms of FM. We included age-matched 302 FM (289 F, 13 M), and 115 (105 F, 10 M) RA patients. All patients were questioned about smoking and the severity of their chronic widespread pain (CWP) and symptoms of FM by using a visual analog scale (VAS, 0-10) and FM impact questionnaire. In addition, patients were asked questions about depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 17 publications
2
23
1
8
Order By: Relevance
“…In addition, the Brazilian study also did not show significant differences in fatigue, depression, and anxiety (components of FIQ) between FMS smokers and FMS non-smokers [18]. However, increased scores for depression and/or anxiety in smoking FMS patients as compared to those of non-smoking patients were identified [16,17]. In the present study, functional assessments for fatigue, depression, and anxiety were also performed.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…In addition, the Brazilian study also did not show significant differences in fatigue, depression, and anxiety (components of FIQ) between FMS smokers and FMS non-smokers [18]. However, increased scores for depression and/or anxiety in smoking FMS patients as compared to those of non-smoking patients were identified [16,17]. In the present study, functional assessments for fatigue, depression, and anxiety were also performed.…”
Section: Discussionmentioning
confidence: 46%
“…A majority of the research has suggested that smoking could influence clinical features and functional impairment in FMS patients [15][16][17]. However, no association between smoking and FMS features was proposed in a clinical study of the Brazilian FMS population [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations